2022
DOI: 10.1016/j.jtumed.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Examining exclusive breastfeeding in Iranian mothers using the five-factor model of personality traits

Abstract: Objectives The initiation of exclusive breastfeeding and its continuation plays a vital role in maternal and child health. This study investigates the prediction of exclusive breastfeeding in Iranian mothers using the five-factor model. Methods A descriptive correlational study was conducted using cluster random sampling. and 120 mothers with children aged 6 to 12 months, referred to health centres of Shiraz University of Medical Sciences in Valfagr and Enghelab in Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
2
2
Order By: Relevance
“…In line with the current study, Brown found that conscientiousness was significantly related to the belief that breastfeeding is a healthy behavior, which increased mothers’ motivation to breastfeed but is not a guarantee of continued breastfeeding [ 37 ]. In contrast with this study that conscientiousness and breastfeeding together improve physical health, Padashian et al and Keller et al demonstrated that there is no relationship between breastfeeding and conscientiousness or situational psychological actions [ 34 , 38 ].…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In line with the current study, Brown found that conscientiousness was significantly related to the belief that breastfeeding is a healthy behavior, which increased mothers’ motivation to breastfeed but is not a guarantee of continued breastfeeding [ 37 ]. In contrast with this study that conscientiousness and breastfeeding together improve physical health, Padashian et al and Keller et al demonstrated that there is no relationship between breastfeeding and conscientiousness or situational psychological actions [ 34 , 38 ].…”
Section: Discussioncontrasting
confidence: 78%
“…Finally, neuroticism and openness experience were other maternal personality traits that were not confirmed in the present study, but Di Mattei et al and Sutin et al demonstrated the influence of these traits on the duration of breastfeeding [ 21 , 38 ].…”
Section: Discussioncontrasting
confidence: 66%
“…This study showed that pregnant women with type D personality had lower breastfeeding competency than others, which could be explained by the influence of negative psychological on breastfeeding. Pregnant women with an extroverted nature have decisiveness and positive emotions, and show more potential in starting or continuing breastfeeding 40 . In contrast, pregnant women with neuroticism, anxiety, and depression shilly-shally to make breastfeeding decisions and have lower breastfeeding competency than others 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Service quality can be improved by increasing the available human resources and without large investments. This increase can reduce maternal and infant mortality and morbidity (Padashian et al, 2021). Article A9 IBCLCs provide instructional support in addition to home visits as well as telephone and text messages to breastfeeding mothers.…”
Section: Synthesis Of Evidencementioning
confidence: 99%